V-modified Co3O4 nanorods with superior catalytic activity and thermostability for CO oxidation. Issue 35 (15th August 2018) - Wang, Kun; Liu, Baolin; Cao, Yali; Li, Yizhao; Jia, Dianzeng
Abstract : Solid-state chemical strategy was applied to synthesize V-modified Co3 O4 nanorods with high catalytic activity and thermostability for CO oxidation. Abstract : It is well known that Co3 O4 nanomaterials with high catalytic activity can be easily deactivated at high temperature, which will further inhibit their practical applications in CO oxidation catalysis. Herein, we report a facile solvent-free strategy to synthesize V-modified Co3 O4 nanorods. The V-modified Co3 O4 nanorods (without pretreatment) showed superior catalytic activity for CO oxidation in normal feed gas, and 100% CO conversion can be achieved at a low temperature of 60 °C. Additionally, the incorporation of V into Co3 O4 nanorods remarkably enhanced the sintering resistance performance at high temperature. Compared with unmodified Co3 O4 nanorods, V-modified Co3 O4 nanorods exhibit outstanding thermostability in the catalysis due to the strong interaction between V and Co. This is promising for the development of practical catalysts for CO oxidation with excellent anti-inactivation performance.